Diabetes distress and related factors in South African adults with type 2 diabetes. Issue 2 (15th July 2016) - Ramkisson, Samantha; Joseph Pillay, Basil; Sartorius, Benn
Abstract : Background: In South Africa, the prevalence rate of diabetes is 9.27%, with an estimated 2.6 million people living with the disease. Diabetes-related distress has been described as encompassing the patient's concerns about the self-management of diabetes, perception of support, emotional burden and access to quality health care. There has been little or no research done in South Africa regarding diabetes-related distress. Objectives: The aim of this paper was: (1) to identify the level of diabetes-related distress in a cohort of diabetes type 2 patients in KwaZulu-Natal and (2) to identify the factors that contribute to diabetes-related distress. Methods: This cross-sectional study was conducted at two public facilities and five private medical practices on the north coast of KwaZulu-Natal, South Africa. The Diabetes Distress Scale was administered, together with a demographic questionnaire, to 401 participants. Results: In total, 44% of the sample reported having moderate to high levels of distress. The mean scores of the Emotional Burden dimension (M = 2.6; SD = 1.42) and the Regimen Distress dimension (M = 2.33; SD = 1.29) suggested moderate levels of distress. Factors that significantly contributed to high levels of distress were younger age, high HbA1C levels, female gender, attending the public health sector, unemployment and being a person of colour. Conclusion: Healthcare providers need to pay particular attention to the psychological needs of the patient, which impact on the medical outcomes of the disease.